Phenotypic Variation of Botrytis cinerea Isolates Is Influenced by Spectral Light Quality - Meng, Lijuan; Mestdagh, Hanna; Ameye, Maarten; Audenaert, Kris; Höfte, Monica; Van Labeke, Marie-Christine (Frontiers in Plant Science, 2020)
Botrytis cinerea, a fungal pathogen that causes grey mold, displays a high degree of phenotypic diversity. Light emitting diodes (LEDs) with specific light spectrum are increasingly used as lighting resource for plant greenhouse production. The chosen light spectrum can also have an effect on the pathogens in this production system. In this study, we investigated the phenological diversity in fifteen B. cinerea isolates upon different light treatments. Daylight, darkness and LED lights with different wavelengths (white, blue, red, blue+red) were chosen as treatments. The fifteen Botrytis isolates differed in their mycelial growth rate, conidia production and sclerotia formation. Light quality had a limited effect on growth rate. All isolates sporulated under daylight treatment, red light resulted in lower sporulation, while white, blue, and blue+red light inhibited sclerotia formation in all isolates, and sporulation in most, but not all isolates. Pathogenicity of the Botrytis isolates was studied on two-week-old strawberry (Fragaria × ananassa ‘Elsanta’) leaves grown under white, blue and red LED lights. The isolates differed in virulence on strawberry leaves, and this was positively correlated to oxalic acid production by B. cinerea in vitro. Red LED light improved leaf basal resistance to all the tested Botrytis isolates. Blue light pretreatment resulted in decreased leaf resistance to some isolates. Furthermore, we used image analysis to quantify the virulence of the different Botrytis isolates based on changes in photosynthetic performance of the strawberry leaves: chlorophyll fluorescence (Fv/Fm), chlorophyll index (ChlIdx) and anthocyanin content (modified anthocyanin reflection index, mAriIdx). Fv/Fm showed a strong negative correlation with disease severity and can be an indicator for the early detection of grey mold on strawberry leaves.